Pemaknaan Potensi Lokal di Desa Wisata Rawabogo Kabupaten Bandung - Alma Verdiana (Jurnal Riset Perencanaan Wilayah dan Kota, 2021)
Abstract. The tourism potential of Rawabogo Village became one of the urgencies after the establishment of the tourism village title in the village. Rawabogo Village, which is located in Ciwidey District, has been designated as a tourism village since 2011 with the potential for the Gunung Nagara Padang Site. However, until now this potential has not shown significant development. Rawabogo Tourism Village needs to explore the meaning of this phenomenon in order to know the real local potential. Based on this phenomenon, the method needed in addition to the instrumental concept (disstantiation) is also required for its meaning (appropriation). This research method uses a symbolic hermeneutic approach (Paul Ricoeur) which offers a new paradigm in the field of tourism village planning. This approach describes the meaning by combining "explanation" and "understanding" of the information unit to produce meaning of local potential through a process of disstantiation and appropriation in accordance with the needs of meaning in the Rawabogo Tourism Village. The results of the analysis resulted in the meaning of the local potential of the Rawabogo Tourism Village, namely culture as the identity of the cultural community and the potential attractiveness of Rawabogo Village, Gunung Nagara Padang as a characteristic of Rawabogo Village, and the diversity of attractions as an opportunity for Rawabogo Tourism Village. The meaning of the local potential can be an option for the direction of the tourism potential of the Rawabogo Tourism Village. Abstrak. Potensi wisata Desa Rawabogo menjadi salah satu urgensi setelah ditetapkannya gelar desa wisata pada desa tersebut. Desa Rawabogo yang berlokasi di Kecamatan Ciwidey telah ditetapkan menjadi desa wisata sejak tahun 2011 dengan potensi adanya Situs Gunung Nagara Padang. Namun hingga kini potensi tersebut belum menunjukkan perkembangan signifikan. Desa Wisata Rawabogo perlu menggali pemaknaan fenomena tersebut agar dapat mengetahui potensi lokal sebenarnya. Berdasarkan fenomena tersebut maka metode yang dibutuhkan selain pada konsep instrumentalnya (distansiasi) diperlukan juga pemaknaannya (apropriasi). Metode penelitian ini menggunakan pendekatan hermeneutik simbolis (Paul Ricoeur) yang menjadi penawaran paradigma baru dalam bidang perencanaan desa wisata. Pendekatan tersebut mendeskripsikan pemaknaan dengan menggabungkan antara “penjelasan” dan “pemahaman” atas unit informasi untuk menghasilkan pemaknaan potensi lokal melalui proses distansiasi dan apropriasi yang sesuai dengan kebutuhan pemaknaan di Desa Wisata Rawabogo. Hasil dari analisis menghasilkan pemaknaan potensi lokal Desa Wisata Rawabogo yaitu budaya sebagai identitas masyarakat budaya dan potensi daya tarik Desa Rawabogo, Gunung Nagara Padang sebagai ciri khas Desa Rawabogo, dan keberagaman daya tarik sebagai peluang Desa Wisata Rawabogo. Pemaknaan potensi lokal tersebut dapat menjadi opsi arah potensi wisata dari Desa Wisata Rawabogo.